2007
DOI: 10.1017/s0272263107070015
|View full text |Cite
|
Sign up to set email alerts
|

THE ACQUISITION OF PROGRESSIVE AND RESULTATIVE MEANINGS OF THE IMPERFECTIVE ASPECT MARKER BY L2 LEARNERS OF JAPANESE: Transfer, Universals, or Multiple Factors?

Abstract: It has been observed that there is a strong association between the inherent (lexical) aspect of verbs and the acquisition of tense-aspect morphology (the aspect hypothesis; Andersen & Shirai, 1994). To investigate why such an association is observed, this study examined the influence of inherent aspect and learners' first language (L1) on the acquisition of Japanese imperfective aspect by using two tasks—an acceptability judgment test and an oral picture description task—with two groups of second langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Many of these studies, however, have shown no clear agreement as to which theoretical explanations should be given to the predictable patterns of acquisition of tense and aspect. Hence, reasons such as the distribution of input (Ayoun and Salaberry 2008;Rhode 1996;Robison 1995;Andersen and Shirai 1994) to which learners are exposed, the influence of the teaching environment (Bardovi-Harlig 1992), L1 influence (Collins 2002(Collins , 2004Sugaya and Shirai 2007) or alternative universal mechanisms (Slabakova 1999;Gavruseva 2002;and Haznedar 2007 for a counterargument) among others, have been advanced in order to provide an explanation for certain robust patterns of the acquisition of tense and aspect morphology. Within the framework of the AH, the goal of this paper is to provide further evidence from cross-sectional data with regard to the acquisition of progressive aspect by learners of English who are bilingual Catalan-Spanish, a language constellation that has not previously been studied in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies, however, have shown no clear agreement as to which theoretical explanations should be given to the predictable patterns of acquisition of tense and aspect. Hence, reasons such as the distribution of input (Ayoun and Salaberry 2008;Rhode 1996;Robison 1995;Andersen and Shirai 1994) to which learners are exposed, the influence of the teaching environment (Bardovi-Harlig 1992), L1 influence (Collins 2002(Collins , 2004Sugaya and Shirai 2007) or alternative universal mechanisms (Slabakova 1999;Gavruseva 2002;and Haznedar 2007 for a counterargument) among others, have been advanced in order to provide an explanation for certain robust patterns of the acquisition of tense and aspect morphology. Within the framework of the AH, the goal of this paper is to provide further evidence from cross-sectional data with regard to the acquisition of progressive aspect by learners of English who are bilingual Catalan-Spanish, a language constellation that has not previously been studied in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers (e.g., Bonilla 2013, Shirai 2004, Sugaya & Shirai 2007 have made reference to the role of task type in explaining differential outcomes in research testing the AH, few studies have empirically tested this claim. In a study comparing accuracy rates across tasks in L2 Spanish, Salaberry & Lopez-Ortega (1998) found that only the lower proficiency group's use of past tense morphology varied between a written narrative and a grammar test (either fill-in-the-blank or multiple choice depending on the group), with more mistakes occurring in the grammar test; the more advanced group scored consistently across tasks.…”
Section: Task Variabilitymentioning
confidence: 99%
“…To our knowledge, there has been little attention paid to specific areas of grammar in previous L2 attrition studies of Japanese returnees. Tomiyama (1999) looked at Japanese child returnees' L2 attrition, but in a qualitative study. There was no focus on grammar per se.…”
Section: L2 Attritionmentioning
confidence: 99%
“…This is not usually discussed in relation to L2 acquisition research since one generally assumes that once learners have reached a certain proficiency in the L2, they will retain that proficiency, but studies dating back to Cole (1929) have been concerned with the loss of foreign language skills by high school students during summer vacation after completing a language course. In more recent L2 attrition studies, researchers have been interested in returnees who have spent longer periods abroad (e.g., Yoshitomi, 1992Yoshitomi, , 1999Tomiyama, 1999Tomiyama, , 2009. Typically, people who stay a number of years in an L2-speaking environment gain a certain level of proficiency.…”
Section: Introductionmentioning
confidence: 99%